Microorganisms and Biostimulants Impact on the Antioxidant Activity of Buckwheat (Fagopyrum esculentum Moench) Sprouts - Robert Witkowicz; Wioletta Biel; Edyta Skrzypek; Joanna Chłopicka; Katarzyna Gleń-Karolczyk; Mateusz Krupa; Ewelina Prochownik; Agnieszka Galanty (MDPI AG, 2020)
The study analyzes the influence of plant growth promoters and biological control agents on the chemical composition and antioxidant activity (AA) in the sprouts of buckwheat. The AA of cv. Kora sprouts was higher than cv. Panda, with 110.0 µM Fe2+/g (FRAP-Ferric Reducing Antioxidant Power), 52.94 µM TRX (Trolox)/g (DPPH-1,1-diphenyl-2-picrylhydrazyl), 182.7 µM AAE (Ascorbic Acid Equivalent)/g (Photochemiluminescence-PCL-ACW-Water-Soluble Antioxidant Capacity) and 1.250 µM TRX/g (PCL-ACL-Lipid-Soluble Antioxidant Capacity). The highest AA was found in the sprouts grown from seeds soaked in Ecklonia maxima extract and Pythium oligandrum (121.31 µM Fe2+/g (FRAP), 56.33 µM TRX/g (DPPH), 195.6 µM AAE/g (PCL-ACW) and 1.568 µM TRX/g (PCL-ACL). These values show that the antioxidant potential of buckwheat sprouts is essentially due to the predominant hydrophilic fraction of antioxidants. The AA of the sprouts was strongly correlated with total polyphenol content.